Health Impacts of Psychosocial Factors among Construction Workers: A Systematic Review - Fajarudin, Khairul; Erwandi, Dadan; Kadir, Abdul (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Psychosocial factors are one of the health determinants in construction activities that can damage physical and psychological conditions through the stress mechanism. This study is intended to investigate the dominant psychosocial factors that deteriorate the health of construction workers by conducting a systematic review. The systematic review was conducted on data collected from journal articles retrieved using 3 library search engines: ProQuest, Scopus, and EBSCO, to enable search through a dozen databases for articles published within the years of 2010 - 2019. The criteria used were articles on construction workers experiencing psychosocial exposure, with either physical or mental health outcomes. It resulted in an analysis of 10 out of 65.797 articles. There were six elements of psychosocial factors analyzed: psychological demand, job demand, job control, job dissatisfaction, work-family conflict, and bullying. The mental health problems identified were stress, psychological distress, presenteeism, and misuse of drugs while the physical health problems discovered were Musculoskeletal disorders, increased blood pressure, increased body mass index, increased fat mass percentage, fatigue, and heat diseases. This study can give insights on psychosocial hazards to organizations which will enable them to determine their focus to minimize deterioration of health among workers.